Implementasi Kebijakan Program Tahfidz Al-Qur’an sebagai Upaya Penguatan Pendidikan Karakter di Pondok Pesantren Al-Qur’an Putri Ibnu Katsir Jember (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2020)
Education which is expected to spearhead the progress of the nation in fact it has not been fully realized. Thousands of Islamic boarding schools spread throughout the regions in Indonesia also has not been able to overcome the problem of character degradation to the optimum. Character education is fundamental in the formation of human personality in order to create a generation that begets God. One of the boarding school which is quite successful in making the memorization program policy as an effort to strengthen character education namely the Islamic women’s Boarding School of Al-Qur’an Ibnu Katsir Jember. Through case study research with nonethnographic data collection techniques, non-participant observation, unstructured interviews, and secondary documents, It was found that the implementation of the memorization of the al-Qur'an program policy as an effort to strengthening then character education done by choosing programs to add to rote, repeat rote, monthly exams, make memorization with friends, make memorization with family and public testing. These activities encourages the strengthening of characters so as to produce self-confidence, tolerance, tough and hardiness, cooperation, and commitment. Keyword: Implementation, Character Education, Program Policy.